2022
DOI: 10.18844/cjes.v17i7.7693
|View full text |Cite
|
Sign up to set email alerts
|

A blended learning approach for teaching computer science in high schools

Abstract: The purpose of this research is to determine the proficiency levels of teachers giving computer education in high schools regarding blended learning. In this study, the competencies of teachers who give computer education in high schools regarding blended learning were handled in accordance with the survey model, which is one of the quantitative research methods. The study group of the research consists of 345 computer teachers who teach in high schools in the city of Almaty, Kazakhstan in the 2021–2022 academ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…However, although blended learning offers various advantages, there are some challenges that need to be overcome in its implementation in mathematics learning. One of the main challenges is the availability of adequate technology infrastructure in students' schools and homes, as well as the digital skills required by both teachers and students (Kadirbayeva et al, 2022). In addition, effective lesson planning and proper integration between online and face-to-face learning also require considerable time and resources (Tabieh &;Hamzeh, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, although blended learning offers various advantages, there are some challenges that need to be overcome in its implementation in mathematics learning. One of the main challenges is the availability of adequate technology infrastructure in students' schools and homes, as well as the digital skills required by both teachers and students (Kadirbayeva et al, 2022). In addition, effective lesson planning and proper integration between online and face-to-face learning also require considerable time and resources (Tabieh &;Hamzeh, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Flexibility in time and place and the use of diverse learning resources is one of the hallmarks of blended learning, allowing adaptation to students' individual learning styles (Ariswan et al, 2023). Through this combination, blended learning not only enables more personalized and student-centered teaching, but also encourages the development of digital and critical skills that are essential in today's information technology era (Bedebayeva et al, 2022;Mutya &;Masuhay, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…This study emphasises the significance of contextual factors, such as cultural and educational frameworks, in influencing the perspectives of individuals on blended learning. In their study, Bedebayeva et al (2022) focused on computer education in Kazakhstan's secondary schools, particularly evaluating teachers' skills. Their study revealed many disparities, including gender differences, in educators' abilities in blended learning environments.…”
Section: Studies On Blended Learningmentioning
confidence: 99%
“…The use of learning resources in the form of interactive multimedia is considered an effective hybrid learning tool (Rukayah et al, 2022). Meanwhile, for educators in particular, training is needed to implement hybrid learning mode well (Bedebayeva et al, 2022). The digital skills of educators are essential to facilitate active engagement in learning (Ng et al, 2022).…”
Section: Introductionmentioning
confidence: 99%